Hormone Resistance in Two MCF-7 Breast Cancer Cell Lines is Associated with Reduced mTOR Signaling, Decreased Glycolysis, and Increased Sensitivity to Cytotoxic Drugs - Leung, Euphemia Yee; Kim, Ji Eun; Askarian-Amiri, Marjan; Joseph, Wayne R.; McKeage, Mark J.; Baguley, Bruce C. (Frontiers in Oncology, 2014)
The mTOR pathway is a key regulator of multiple cellular signaling pathways and is a potential target for therapy. We have previously developed two hormone-resistant sub-lines of the MCF-7 human breast cancer line, designated TamC3 and TamR3, which were characterized by reduced mTOR signaling, reduced cell volume, and resistance to mTOR inhibition. Here, we show that these lines exhibit increased sensitivity to carboplatin, oxaliplatin, 5-fluorouracil, camptothecin, doxorubicin, paclitaxel, docetaxel, and hydrogen peroxide. The mechanisms underlying these changes have not yet been characterized but may include a shift from glycolysis to mitochondrial respiration. If this phenotype is found in clinical hormone-resistant breast cancers, conventional cytotoxic therapy may be a preferred option for treatment.